First Record of the Caspian Tern Hydroprogne caspia (Charadriiformes: Laridae) in Kalimantan, Indonesia, with A Review of Its Status Across Borneo - Teguh Willy Nugroho; Muhammad Rochim; Ratna Mariana; Eko Jati Sujiyanto; Hariyadi; Sulton Mubarok; Mika Tambing Pairunan (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
The Caspian Tern Hydroprogne caspia is a cosmopolitan migratory waterbird and an uncommon non-breeding visitor in Indonesia. Although previously recorded from Sabah, Sarawak, and Brunei Darussalam, the species had not been documented from Indonesian Borneo. Here, we report the first confirmed record of H. caspia in Kalimantan, Indonesia. On 2 February 2026, two individuals were observed and photographed on the intertidal mudflats of Kempeng Beach, Central Kalimantan, during the Asian Waterbird Census. Identification was based on their exceptionally large size, massive deep-red bill, and characteristic non-breeding plumage. A review of published literature and citizen-science databases indicates that this record represents a significant southward extension of the species’ documented distribution on Borneo. This finding fills an important geographic gap in the known occurrence of H. caspia within the East Asian–Australasian Flyway and highlights the importance of southern Borneo’s coastal wetlands for migratory waterbirds.